Prevalence and mobility of integrative and conjugative elements within a Streptomyces natural population - Caroline Choufa; Abdoul-Razak Tidjani; Abdoul-Razak Tidjani; Anthony Gauthier; Manar Harb; Manar Harb; Julie Lao; Nathalie Leblond-Bourget; Michiel Vos; Pierre Leblond; Cyril Bontemps (Frontiers in Microbiology, 2022)
Horizontal Gene Transfer (HGT) is a powerful force generating genomic diversity in bacterial populations. HGT in Streptomyces is in large part driven by conjugation thanks to plasmids, Integrative and Conjugative elements (ICEs) and Actinomycete ICEs (AICEs). To investigate the impact of ICE and AICE conjugation on Streptomyces genome evolution, we used in silico and experimental approaches on a set of 11 very closely related strains isolated from a millimeter scale rhizosphere population. Through bioinformatic searches of canonical conjugation proteins, we showed that AICEs are the most frequent integrative conjugative elements, with the central chromosome region being a hotspot for integrative element insertion. Strains exhibited great variation in AICE composition consistent with frequent HGT and/or gene loss. We found that single insertion sites can be home to different elements in different strains (accretion) and conversely, elements belonging to the same family can be found at different insertion sites. A wide variety of cargo genes was present in the AICEs with the potential to mediate strain-specific adaptation (e.g., DNA metabolism and resistance genes to antibiotic and phages). However, a large proportion of AICE cargo genes showed hallmarks of pseudogenization, consistent with deleterious effects of cargo genes on fitness. Pock assays enabled the direct visualization of conjugal AICE transfer and demonstrated the transfer of AICEs between some, but not all, of the isolates. Multiple AICEs were shown to be able to transfer during a single mating event. Although we did not obtain experimental evidence for transfer of the sole chromosomal ICE in this population, genotoxic stress mediated its excision from the chromosome, suggesting its functionality. Our results indicate that AICE-mediated HGT in Streptomyces populations is highly dynamic, with likely impact on strain fitness and the ability to adapt to environmental change.